Evaluating the impact of COVID-19 on pension systems in Latin America and the Caribbean: The case of Argentina - Rafael Rofman; Joaquín Bali\~na; Emanuel López Méndez (Inter-American Development Bank (IDB), 2022)
This paper presents a first approximation to assess the impact of the COVID-19 outbreak on Argentina's pension system in both the short and medium/long-term. To this end, we have used the Pension Projection Model of the Inter-American Development Bank (IDB) to design and analyze possible scenarios and outcomes, based on alternative scenarios. According to the data analyzed and the projections, the impact of COVID-19 on Argentina's pension system in the short run seems to have been limited, particularly given the rapid recovery during the last months of 2021. The long-term impact is harder to predict. Given the macroeconomic effects of the efforts made by authorities to protect the system and pensioners during the pandemic on the one hand; and the effects of COVID19 within the labor market on the other, overall consequences are still to be fully understood.
Keywords: I31; I38; J11; J14; 330; COVID-19; Pension system in Argentina; Short-Term and LongTerm Impacts; IDB projection model